Lecturers in the field of health Sciences at the University of Granada facing the european convergence process: a study of their expectations and training necessities - María José Latorre Medina; Francisco Javier Blanco Encomienda (Revista Electrónica Interuniversitaria de Formación del Profesorado)
The research we present is framed within a larger research project carried out by a group of university teachers at the University of Granada and financed by the Spanish Government during the period 2004-2007 (Ref. SEJ2004-08035-C02-02). In particular, the study focuses on lecturers at this university teaching courses in degrees within the field of Health Sciences. The main purpose is to highlight the necessities and expectations which university teachers who develop their professional activity in this field of knowledge perceive in relation to their professional qualification to enter into the European Higher Education Area, an issue of special relevance to face the new professional challenges.